2018
DOI: 10.7819/rbgn.v20i1.3688
|View full text |Cite
|
Sign up to set email alerts
|

Organizational culture and relationship marketing: an interorganizational perspective

Abstract: Purpose -This paper aimed to analyze the contribution of interorganizational relationships, specifically between suppliers and clients, to organizational cultural changes.Design/methodology/approach -A qualitative multiple case study in two marketing channels was performed, through in-depth interviews, observation and data analysis based on grounded theory.Findings -The contribution of trust, commitment, cooperation and learning processes has been identified in the organizational cultural changes and in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
0
12
0
10
Order By: Relevance
“…As Sarkar, Echambadi, Cavusgil, and Aulakh (2001), Fernández and Martín (2006), and Larentis, Antonello, and Slongo (2018) show, the quality of the relationship between partners, based on trust and commitment, facilitates the establishment of long-term partnership agreements and is considered essential to the success of the cooperation.…”
Section: Inter-firm Cooperation and External Relationsmentioning
confidence: 99%
“…As Sarkar, Echambadi, Cavusgil, and Aulakh (2001), Fernández and Martín (2006), and Larentis, Antonello, and Slongo (2018) show, the quality of the relationship between partners, based on trust and commitment, facilitates the establishment of long-term partnership agreements and is considered essential to the success of the cooperation.…”
Section: Inter-firm Cooperation and External Relationsmentioning
confidence: 99%
“…However, CRM should be viewed as a competitive strategy that addresses the needs of consumers and integrates the way they interact with the organization (Larentis, Antonello and Slongo, 2018). CRM should also be a streamlined business process that delivers value to customers, employees, and stakeholders (Grant, 2017).…”
Section: Literature Review 21 Customer Relationship Management (Crm)mentioning
confidence: 99%
“…This shows the crucial importance of CRM is to an airline's success. Supporting this was research from Larentis et al (2018) which investigated organizational culture and relationship marketing (RM) and stated that RM aims to generate long-term profitable relationships between partners. As such, far too many airlines have equated their CRM process with their frequent flyer program (FFP).…”
Section: Customer Relationship Management (Crm)mentioning
confidence: 99%
“…On the basis of the results of the research, the authors state that universities and research institutes should draft and implement guidelines where leaders with certain traits and norms can play a role to nourish an environment where stakeholders think outside the box, with learning and knowledge creation and proactive contribution beyond responsibilities, obligations and compulsion Article [29] Authors research the contribution of interorganizational relations (including suppliers and customers) to the organizational cultural change. It was found that interorganizational culture is developed as a system of symbols and meanings, which is shared by groups of different organizations or persons during the transition period, because cultural fragmentation perspectives are predominant Article [30] The author draws attention to the fact that religion is a pervasive organizing framework and in terms of communication, its role in the socialization processes has to be understood and evaluated…”
Section: Document Type Sourcementioning
confidence: 99%